2016
DOI: 10.1080/13803395.2015.1123225
|View full text |Cite
|
Sign up to set email alerts
|

The role of attention in emotional memory enhancement in pathological and healthy aging

Abstract: After short delays between encoding and retrieval, healthy young participants have better memory performance for emotional stimuli than for neutral stimuli. Divided-attention paradigms suggest that this emotional enhancement of memory (EEM) is due to different attention mechanisms involved during encoding: automatic processing for negative stimuli, and controlled processing for positive stimuli. As far as we know, no study on the influence of these factors on EEM in Alzheimer's disease (AD) and mild cognitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 80 publications
1
7
0
Order By: Relevance
“…To our knowledge, this is the first study examining selective memory for emotional scenes in patients with MCI (but see Gorenc-Mahmutaj et al (2015) and Sava et al (2016)) for memory for complete emotional images in patients with MCI or dementia). The primary goal of the study was to examine the effect of emotion on selective scene memory between MCI patients and healthy older adults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, this is the first study examining selective memory for emotional scenes in patients with MCI (but see Gorenc-Mahmutaj et al (2015) and Sava et al (2016)) for memory for complete emotional images in patients with MCI or dementia). The primary goal of the study was to examine the effect of emotion on selective scene memory between MCI patients and healthy older adults.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies of working memory for emotional images have revealed a negativity bias in the memories of MCI patients (but the negative items were also more arousing than positive items, making it impossible to attribute these differences to valence (how positive or negative) alone (Dohnel et al, 2008, 2007)). Another investigation of MCI patients’ recognition memory for emotional and neutral IAPS images showed higher true recognition and false alarms for negative compared to positive or neutral images, and also that dividing attention did not impact discrimination ability (Sava et al, 2016). In other studies MCI patients have shown a memory benefit for positive or negative words (Brueckner and Moritz, 2009; Callahan et al, 2016), but impaired memory for faces studied with emotional expressions (Wang et al, 2013; Werheid et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Further, patients with AD committed more causal errors for positive and negatively valanced scripts than for neutral scripts, which suggests that their memory for pictorial information is vulnerable to distortions due to emotional valence. This finding that patients with AD demonstrate increased memory errors to emotionally valanced pictures has been replicated when attention at encoding was manipulated (Sava, Paquet, Dumurgier, Hugon, & Chainay, 2016).…”
Section: The Effect Of Emotion On False Memoriesmentioning
confidence: 83%
“…On the contrary, incidental encoding occurs under divided attention (Trivedi et al 2011). For instance, young adults discriminated equally between old and new images in the full and divided attention condition; however, this pattern was altered in normal aging and neurodegenerative disease according to the attention resources available at encoding (Sava et al 2016). Other studies have shown that dividing attention during encoding can disrupt memory enhancement for nonarousing emotional items but not emotionally arousing items for reasons that are not well understood (Kensinger 2004).…”
Section: Introductionmentioning
confidence: 95%
“…The latter is particularly relevant when retrieval occurs immediately after encoding, thereby eliminating the influence of consolidation. A previous study has shown that EEM in healthy young adults is due to different attention mechanisms activated during encoding: automatic processing (incidental) for negative stimuli and controlled processing (intentional) for positive stimuli (Sava et al 2016). Intentional encoding refers to self-directed or controlled situations where there is an explicit attempt made and full attention devoted to encoding new episodic information.…”
Section: Introductionmentioning
confidence: 99%